Comparison of dental arch dimensions in models of preschool children with cleft lip/palate repaired by means of surgery alone versus controls. Issue 3 (September 2016) - Burhan, Ahmad S.; Nawaya, Fehmieh R.
Abstract : Background: Cleft lip and palate (CLP) anomaly is one of the most prevalent congenital defects causing disturbances of dental arch dimensions. This study aimed at investigating differences in these dimensions between preschool children with cleft lip/ palate and a matched control group representing healthy individuals with normal occlusion (NO). Materials and methods: The sample of this cross-sectional analytical study consisted of 108 plaster models of children aged from 4 to 5.5 years. They were divided into five groups: the cleft lip group, the cleft palate (CP) group, the unilateral cleft lip and palate group, the bilateral cleft lip and palate group, and the NO group. The NO group was used as a control group. All cleft-affected children were treated only with surgery. Dental arch length and widths were measured. Results: The dental arch dimensions of the cleft lip group were nearly similar to those in the controls. Moreover, the mandibular transverse widths of the CP group were close to those in the controls. However, the mandibular arch length and all maxillary dimensions of the CP group were smaller than those in the controls. In the unilateral cleft lip and palate group, the arch lengths in both jaws and the maxillary transverse widths were smaller than those in the controls, whereas the mandibular transverse widths were similar to those in the controls. In the bilateral cleft lip and palate group, the arch lengths in both jaws were close to those in the controls, but both arches were narrower than those in the controls. Conclusion and recommendations: The various types of CLP were found to be associated with differences in most maxillary and some mandibular arch dimensions. These data can be used for cleft patient counseling and treatment planning.